2011
DOI: 10.11650/twjm/1500406372
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical Orthogonality Relations for Continuous q-Jacobi Polynomials

Abstract: We consider the continuous q-Jacobi polynomials {Pn=0 , extending the variable and the parameters beyond classical considerations. For those new allowed values of the parameters for which Favard's theorem fails to work, we construct inner products in which the presence of the Askey-Wilson divided difference operator provides the q-Sobolev character of the non-standard orthogonality for the corresponding family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A slightly less detailed study of orthogonality conditions for the big q-Jacobi polynomials can be found in [17], using a bilinear form instead of the linear form L 0 .…”
Section: The Big Q-jacobi Polynomialsmentioning
confidence: 99%
See 3 more Smart Citations
“…A slightly less detailed study of orthogonality conditions for the big q-Jacobi polynomials can be found in [17], using a bilinear form instead of the linear form L 0 .…”
Section: The Big Q-jacobi Polynomialsmentioning
confidence: 99%
“…the operator T in Theorem 2.2 can be chosen as D q −1 , and condition (7) holds (see the relation between q-Hahn and big q-Jacobi polynomials and the expression (19) for the coefficients γ n ). Also, for n ≥ N ,…”
Section: The Orthogonality Conditions For |Q| <mentioning
confidence: 99%
See 2 more Smart Citations
“…A slightly less detailed study on orthogonality conditions for the big q-Jacobi can be found in [27].…”
Section: The Big Q-jacobi Polynomialsmentioning
confidence: 99%